2021
DOI: 10.20473/jvhs.v5.i2.2021.87-93
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Stress, Anxiety, and Depression Levels of Students in Preparation for the Exit Exam Competency Test

Abstract: Background: Permendikbud No.2 of 2020 regulates student competency test in the health sector. The exit exam competency test is a requirement that must be met by students after completing all stages of education in order to get a certificate and Surat Tanda Registrasi (STR). The results of the preliminary study show that although there is a high chance of passing the exit exam competency test at the RMIK (Medical Records and Health Information) Study Program at Esa Unggul University (UEU), some of the students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
1
1
0
4
Order By: Relevance
“…This research is supported by previous research conducted [15]using the Depression Anxiety Scale (DASS) score, which shows that most elderly experience a relatively mild level of Anxiety. The findings from this study are the results of research conducted, by [16]which revealed that the majority of the elderly experienced different levels of Anxiety, namely moderate anxiety levels in as many as 26 people (46.4%), high anxiety levels in as many as 21 people (37.5%), and severe anxiety level as many as two people (3.6%).…”
Section: Resultssupporting
confidence: 83%
“…This research is supported by previous research conducted [15]using the Depression Anxiety Scale (DASS) score, which shows that most elderly experience a relatively mild level of Anxiety. The findings from this study are the results of research conducted, by [16]which revealed that the majority of the elderly experienced different levels of Anxiety, namely moderate anxiety levels in as many as 26 people (46.4%), high anxiety levels in as many as 21 people (37.5%), and severe anxiety level as many as two people (3.6%).…”
Section: Resultssupporting
confidence: 83%
“…Test the reliability of measuring instruments using Cronbach's alpha. Reliability test results obtained on 3 of the 14 items of the DASS 42 questionnaire showed stress = 0.951, anxiety = 0.943, and depression = 0.952 [18].…”
Section: Methodsmentioning
confidence: 95%
“…Berdasarkan S. Lovibond, P. Lovibond tahun 1995 yang mengelompokkan tingkat stress menjadi normal, ringan, sedang, berat, dan sangat berat. (5) Berdasarkan penelitian Afryan et al (2019), mengatakan bahwa tingkat stres yang dialami dikelompokkan menjadi tingkat stres sedang (53,1%), stres ringan (40,7%) dan tingkat stres berat (6,2%) akibat mengerjakan tugas akhir. (6) Faktor yang berhubungan dengan tingkat stres mahasiswa dalam penyusunan skripsi ada faktor biologis dan factor psikologis.…”
Section: Pendahuluanunclassified